PANoptosis Regulation in Reservoir Hosts of Zoonotic Viruses - Anantika Chandra; Sannula Kesavardhana (Viruses)
Zoonotic viruses originating from reservoir hosts, such as bats and birds, often cause severe illness and outbreaks amongst humans. Upon zoonotic virus transmission, infected cells mount innate immune responses that include the activation of programmed cell death pathways to recruit innate immune cells to the site of infection and eliminate viral replication niches. Different inflammatory and non-inflammatory cell death pathways, such as pyroptosis, apoptosis, necroptosis, and PANoptosis can undergo concurrent activation in humans leading to mortality and morbidity during zoonosis. While controlled activation of PANoptosis is vital for viral clearance during infection and restoring tissue homeostasis, uncontrolled PANoptosis activation results in immunopathology during zoonotic virus infections. Intriguingly, animal reservoirs of zoonotic viruses, such as bats and birds, appear to have a unique immune tolerance adaptation, allowing them to host viruses without succumbing to disease. The mechanisms facilitating high viral tolerance in bats and birds are poorly understood. In this perspective review, we discuss the regulation of PANoptotic pathways in bats and birds and indicate how they co-exist with viruses with mild clinical signs and no immunopathology. Understanding the PANoptotic machinery of bats and birds may thus assist us in devising strategies to contain zoonotic outbreaks amongst humans.